Kajian penggunaan obat anti emetik pada pasien lnh di ruang one day care RSUP Dr. M Djamil Padang - Nasif, Hansen; Sartika, Lia; Sari, Yelly Oktavia (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
In the treatment of non-Hodgkin's lymphoma, a combination of chemotherapy drugs (Cyclophospamide, Doxorubicin, Vincristine, and Prednisone) is commonly used. Chemotherapy can lead to side effects such as nausea and vomiting, which can be uncomfortable for patients and may interfere with their treatment. This study aimed to analyze the usage pattern of antiemetics, the compatibility of antiemetics with the emetogenic risk of combination chemotherapy, and the relationship between antiemetic dosage suitability and RINVR scores (Rhodes Index Nausea Vomiting and Retching). The RINVR instrument consists of 8 questions, which evaluates the duration, frequency, amount/volume, and stress related to nausea or vomiting. The study involved 30 patients and data were collected through telephone interviews and patient's medical records. Statistical tests using the independent T test showed mild nausea and vomiting (0-8) for both acute and delayed symptoms against the condition of post-chemotherapy. A normality of RINVR scores was tested and it was determined that the scores were not normally distributed (p<0.05). In bivariate analysis, it was found that the average RINVR scores for both acute and delayed symptoms did not show statistically significant differences (p>0.05). This suggests chemotherapy with emetogenic combination still causes nausea and vomiting even though appropriate antiemetics have been given.